Effect of high-fat or high-carbohydrate diets on endurance exercise: A meta-analysis - Erlenbusch, M.; Haub, M.; Munoz, K.; McConnie, S.; Stillwell, B. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The purpose of this investigation was to clarify, via a meta-analysis, whether the literature favors a high-fat or a high-carbohydrate diet to yield superior endurance exercise performance. Twenty published trials were analyzed to compare exercise performance under different diets. The average effect size of -0.60 indicated that subjects following a high-carbohydrate diet exercised longer until exhaustion. The training status of subjects (trained vs. untrained) was significantly related to effect size (r = -0.576, P < 0.01) and effect sizes separated between trained and untrained subjects were -0.05 and -2.84 respectively. The test for homogeneity revealed significant heterogeneity among effect sizes (c2 [19] = 43.30, P < 0.05), indicating all of the trials are not describing the same effect. Given this significant heterogeneity, a conclusive endorsement of a high-carbohydrate diet based on the literature is difficult to make. Highly dissimilar trial protocols are the primary reason for heterogeneity.